Investigating Earth surface deformation with SAR interferometry and geomodeling in the transborder Meuse–Rhine region - Schlögel, Romy; Owczarz, Karolina; Orban, Anne; Havenith, Hans-Balder (Frontiers in Remote Sensing, 2024)
Introduction: This study aims to differentiate local and regional ground uplift, as well as sub-regional subsidence induced by groundwater level drawdown, which are possibly enhanced across fault structures, as monitored by various synthetic aperture radar interferometry (InSAR) processing methods. A buoyant mantle plume under the Eifel may be responsible for the regional ground uplift, including the Weser–Geul (BE) and South Limburg regions (NL), which could negatively affect the area proposed for the future Einstein Telescope. Methods: Different InSAR processing techniques are compared to evaluate their limits in tracking fault structures on a time series of Copernicus Sentinel-1 images while detecting and measuring ground motion based on their phase signature. The results present an overall stable ground for the Euregio Meuse–Rhine region, especially at the Belgian–Dutch border, while tectonic activity is observed along the German side of the Rhine Graben. Results: As the current neotectonic activity in the target area was not well known, we performed a spatiotemporal analysis of ground deformation associated with the presence of NW–SE-trending normal faults where karst also develops, as well as along the Variscan NE–SW-trending thrust faults. This work demonstrates that the identification of deformation hazards using satellite remote sensing (and connected seismological) techniques is challenging mainly due to (very) small regional scale deformation, terrain conditions, and SAR properties. Discussion: Thus, the results mostly indicate ground stability over the area; however, also some agricultural activities were observed, as was deformation along some infrastructure such as railways. Displacements of millimetric order measured along the faults located near the Geul valley (BE) are probably related to old mining activities.